THE PHILOSOPHICAL ESSENCE OF HUMANISTIC IDEAS IN THE SPIRITUAL HERITAGE OF JADID THINKERS (American Journal of Research in Humanities and Social Sciences, 2023)
The article analyzes the views of representatives of the Turkestan Jadids on humanistic ideas. The study of the content, essence and conceptual meaning of the social ideas of the Jadids, such as the concept of national awakening and socio-economic development, teaching young people modern sciences for the improvement of society through education, the creation of new textbooks and theatres takes the main place. The author studied the theoretical and practical aspects of the ideas of youth promoted by the Jadids about obtaining secular science and professional qualifications in foreign countries. The views of the educators of the Jadids on honouring the Motherland, the use of humane ideas for national development, as well as opinions on the social and economic factors of the country's development are studied.